Triśera saśastra abhyutthāna - Das, Asha, 1927- (Bāṇī Dāśa : paribeśaka De Buka Sṭora, 1980)
Evaluation of the militant nationalist movement of the thirties in Bengal, a phase in the Indian freedom movement, and the role and philosophy of the Indian Republican Army under the leadership of Surya Sen, 1892-1934.